Integration of click chemistry and graphene driven molecular design: A mechanistic standpoint on targeted cancer therapeutics - Tewari, Devesh; Choudhary, Neeraj; Tiwari, Himani; Chetna, Tewari; Rawat, Kundan Singh; Rana, Sravendra; Jung, Yong Chae; Sahoo, Nanda Gopal (ELSEVIER, 2025)
Cancer therapeutics require a deep understanding of molecular mechanisms and novel drug delivery approaches. Click chemistry, a powerful tool for the rapid and efficient formation of covalent bonds emerged as a cherished technique for designing and synthesizing molecular probes. The present paper explores the potential of click chemistry with graphene modifications for possible cancer therapeutics for the first time. Diverse click reactions is discussed that are employed in the synthesis of molecular probes using graphene as a platform for drug delivery and imaging. The paper highlights recent advances in the application of click chemistry and graphene modifications for the design of targeted therapeutics that selectively inhibit cancer cell growth and survival. A possible approach of targeting various cancer signaling pathways based on graphene-coupled drug delivery techniques along with challenges and opportunities associated with the use of these molecular design strategies for the development of personalized cancer therapies is also discussed in detail.